Menyoal Kontekstualisasi Hukum Islam tentang Poligami - Ahmad Khoirul Fata; Mustofa Mustofa (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This paper proposes an idea of revitalization. This idea is based on by looking at the lawsuits occurred within the Islamic laws related to family, especially poligamy. This is proposed because polygamy is believed no longer relevant with the changing times which now requires equality of between man and woman. To address this problem, some ideas put forward to reform and re-interpretate some Islamic laws which lays into two major epistemologies: first, contextual interpretation over the texts which are the basis of the implementation of poligamy which in turn was not the core mission of Islam. Meanwhile, it is believed that the fundamental goal of marriage in Islam monogamous. The justification of poligamy by putting forward the texts do not eliminate but gradually endorse the practices of polygamy itself. Therefore, there is still a room to critique the context of polygamy by contextualizing the polygamy laws in which most previous studies were not objective and tend to justify the dominant discoureses on gender relation.